Comparing alternative design options for chronic disease prevention interventions. (January 2015) - Golfam, Mohammad; Beall, Reed; Brehaut, Jamie; Saeed, Sara; Relton, Clare; Ashbury, Fredrick D.; Little, Julian
Abstract Background While the randomized clinical trial is considered to provide the highest level of evidence in clinical medicine, its superiority to other study designs in the context of prevention studies is debated. The purpose of this review was (i) to gather evidence about challenges facing both randomized controlled trials and observational designs for the conduct of population‐based chronic disease prevention interventions and (ii) to consider the suitability of recently proposed hybrid designs for population‐based prevention intervention studies. Methods Rapid review methods were employed for this study. Articles published within 2007‐2012, were included if they: (i) discussed challenges or benefits related to any intervention study design, (ii) compared randomized controlled trials (RCT) and observational designs or (iii) introduced a new study design potentially applicable to population‐based interventions. After initial screening, papers retained for inclusion were subjected to content analysis and synthesis. Results A total of 35 included articles were reviewed and used for synthesis. Both RCTs and observational studies are subject to multiple challenges, the main being external and internal validity for RCTs and observational designs, respectively. Four new hybrid designs identified. Conclusion Although any high quality design can produce high level of evidence, multiple challenges with prevention intervention RCTs or observational studies identified. New hybrid designs that carry benefits of randomized and observational methods may be the road ahead for to assess the effects of population‐based interventions.